PENGEMBANGAN BAHAN AJAR IPS BERBASIS 21St CENTURY SKILLS (4 LEARNING SKILLS) BAGI SISWA SMP/MTs. - Anindya Fajarini; Fikri Apriyono (Jurnal Penelitian dan Pendidikan IPS, 2024)
This study aims to develop teaching materials that represent 21st Century skills (4 Learning Skills). This research is a type of development research (Research and Development). The development model used is the Borg & Gall model. Quantitative data was obtained from a product development assessment questionnaire by material experts, design experts, linguists and users (teachers and students), while qualitative data was obtained through filling in comments and suggestions, both from experts and users. Quantitative data analysis uses descriptive percentage techniques, namely the number of respondents' answers in one item divided by the number of ideal answers in one item. The results showed that the module prepared had a suitability from material experts of 94.28%, from design experts obtained a percentage of 93.75%, from linguists obtained a percentage of 89.33% which means that the language module is valid or suitable for use. The individual test results obtained a percentage of 84.44%, the results of testing the effectiveness of the use of modules obtained from teacher and student responses obtained a percentage of 89.33% and 89.19% which means the module has good effectiveness. Thus, social studies teaching materials in the module is valid and feasible to use to support social studies learning. Recommendations for further research are to develop similar modules with different learning objective and conduct product trials on a wider scale (dissemination)